Kajian Sosiologi Seni Buku Foto “Estetika Banal” Karya Erik Prasetya - Aji Susanto Anom (AKSA: Jurnal Desain Komunikasi Visual, 2018)
Erik Prasetya's photography book "Estetika Banal" is one of the unique objects of photography art and has its own value in the constellation of Indonesian photography book works. This photography book is an object of art whose value is formed by the social process of the photographer as well as the involvement of his supportive community. Assessment with the main theory of art sociology Howard S. Becker and Vera L. Zolberg which the author did will give answers to the phenomenon of explosion of photography books in terms of sales and also provide an understanding of the background of the formation of Erik Prasetya figure and the work of the creation of "Aesthetics Banal". By understanding the workings of the social process on an object of art, sifting through the apparatus that seeks collectively, creates the understanding that an artist can not stand alone. The key to the success of an artist and his work is the collective efforts of the various actors who perform their functions and emphasize the value of a work of art.